Pengaruh Terpaan Iklan Bukalapak di Televisi dan Promosi Penjualan terhadap Keputusan Pembelian di Situs Jual Beli online Bukalapak - Reynald Sukma Adhy, Muhammad Adrian; Widowati Herieningsih, Sri (Interaksi Online, 2019)
Advertising on television and sales promotion is a marketing strategy that is currently being chosen by e-commerce companies to attract consumers to transact, one of which is Bukalapak, which in 2018 had the highest television advertising expenditure and often did sales promotions. However, Bukalapak has not managed to reach the top position as an online buying and selling site chosen by the public. The purpose of this study was to determine the effect of exposure to advertising and sales promotions on purchasing decisions on the Bukalapak online buying and selling site. The theory used in this research is advertising exposure theory and behavioral learning theory. The sample technique used is Non-Probability Sampling. The number of samples in this study were 70 respondents with the characteristics of men and women who live in the city of Semarang knowing Bukalapak advertisements and knowing Bukalapak sales promotions. Analysis of the data used in this study is a linear regression test. The results showed that advertising exposure on purchasing decisions had a significant effect, where the significance value, which means that there was an influence of advertising exposure on television on purchasing decisions in Bukalapak and the coefficient of regression toward Bukalapak advertising exposure on television amounted to which showed a positive effect and advertising exposure variables in television has a significant influence on purchasing decisions by 47.6%. Furthermore, sales promotions on purchasing decisions also have a significant influence where the significance value is strong. It means that there is an influence of sales promotion exposure on buying decisions in Bukalapak and the coefficient of regression direction of exposure to Bukalapak sales promotion amounted to which shows a positive influence and the variable of the sales promotion has influence on purchasing decision by 60.7%.